1989
DOI: 10.1002/j.1460-2075.1989.tb08345.x
|View full text |Cite
|
Sign up to set email alerts
|

A protein induced by NGF in PC12 cells is stored in secretory vesicles and released through the regulated pathway.

Abstract: We have previously described the isolation of a cDNA clone corresponding to an mRNA rapidly induced to high levels in PC12 cells by treatment with NGF. We report here the complete amino acid sequence of the protein (named VGF8a) as deduced by nucleotide sequencing of overlapping cDNA clones. VGF8a is particularly rich in proline residues and has a conspicuous number of short stretches of basic amino acid residues which may represent potential targets for proteolytic cleavage. Antibodies directed against recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 35 publications
5
92
0
Order By: Relevance
“…The present result provides a further clear-cut example of a differential regulation of these peptides costored within the same organelle [30]. An analogous behaviour to secretogranin II has recently been found for another protein apparently stored in large dense core vesicles of PC12 cells [31].…”
Section: Discussionsupporting
confidence: 80%
“…The present result provides a further clear-cut example of a differential regulation of these peptides costored within the same organelle [30]. An analogous behaviour to secretogranin II has recently been found for another protein apparently stored in large dense core vesicles of PC12 cells [31].…”
Section: Discussionsupporting
confidence: 80%
“…This result suggests that di erentiation is dependent upon reasonable amounts of trk being expressed by the cells. To determine if the morphological di erentiation observed at 328C in PC12trk ts p53 cells in the absence of NGF stimulation had characteristics similar to NGF mediated di erentiation, the induction of a speci®c protein marker for di erentiation, VGF, was examined (Possenti et al, 1989). Double transfectants grown at 328C were positive for VGF-antigen immunostaining in a pattern similar to that induced by NGF treatment (Possenti et al, 1989) in control PC12trk cells (data not shown).…”
Section: Analysis Of Pc12 Cells Expressing Trk and Ts P53mentioning
confidence: 95%
“…Chromogranin B is detectable in many of the cells (70%) and shows an even distribution over the cytoplasm. Another secretory protein, (VGF8) (Possenti et al, 1989) was instead absent.…”
mentioning
confidence: 99%